Kecerdasan Emosional dan Tingkat Stres Akademik Mahasiswa Keperawatan pada Pembelajaran Daring Saat Pandemi Covid-19 - Tirta Adikusuma Suparto; Asih Purwandari Wahyoe Puspita; Afianti Sulastri; Andria Pragholapati (NHM PRESS, 2021)
Background: One of the impacts of the COVID-19 pandemic on the academic atmosphere is by changing the learning system from offline to online. Technological sophistication does not always have a positive impact on students, but has a negative impact as well. Problems that can arise during the adaptation process to these changes include academic stress which in turn can affect the physical, psychological, and student achievement. To be able to maintain their achievements, students are required to have the ability to manage academic stress, one of which is good emotional intelligence. Objective: This study aims to identify the relationship between emotional intelligence and students' academic stress levels when carrying out online learning during the covid-19 pandemic. Methods: This research was conducted between June-October 2021 using a Cross-Sectional Survey of all students of the DIII Nursing Study Program, Faculty of Sport and Health Education, Universitas Pendidikan Indonesia (127 nursing students) and analyzed using the Pearson Product Moment correlation technique analysis. Results: The findings of this study are that there is an inverse and significant relationship (p = 0.006 and r = -0.243, ) between emotional intelligence and academic stress in students. The higher the individual's emotional intelligence, the lower the level of academic stress. Conclusion: This study can prove that one of the variables that can affect academic stress is emotional intelligence, so it is important to improve students' emotional intelligence, one of which is emotional intelligence training.